Assessment of quality of care of diabetic patients by health-care professionals in a city – A community-based cross-sectional study - Rajendra Tulank Ankushe; Mohan Kodiba Doibale; Purushottam Kumar (Asian Journal of Medical Sciences, 2023)
Background: Diabetes is undoubtedly one of the most challenging health problems of the 21st century. Patients from poor parts of the Indian urban population do not frequently have access to these health benefits despite having access to reliable screening methods and antidiabetic drugs. Hence, this study was designed to assess the quality of care of diabetic patients by health-care professionals in a city.